Systematic Analysis of Expression Profiles and Prognostic Significance for FAM83 Family in Non-small-Cell Lung Cancer - Gan, Junqing; Meng, Qingwei; Li, Yanjing (Frontiers in Molecular Biosciences, 2020)
Background: Lung cancer is a common malignancy and the leading cause of cancer-related deaths worldwide. Although dramatic progress made in multimodal therapies, it still has a poor prognosis. The Family with sequence similarity 83 (FAM83) of poorly characterized proteins are defined by the presence of the conserved DUF1669 domain of unknown function at their N-termini, most of which are frequently dysregulated in a wide range of cancers. However, the expression and prognostic values of different FAM83 family in lung cancer, especially in non-small-cell lung cancer (NSCLC), have not been clarified. Methods: ONCOMINE, UALCAN, GEPIA, Kaplan-Meier Plotter, cBioPortal, STRING databases were utilized in this study Results: The transcriptional levels of FAM83A/B/C/D/F/G/H were over-expressed in patients with NSCLC. A significant correlation was found between the over-expressions of FAM83A/B/D/F/H and clinical cancer stages in NSCLC patients. Besides, higher mRNA expressions of FAM83A/B/C/D/F/H were found to be significantly associated with overall survival (OS) in lung cancer patients, furthermore, FAM83A, FAM83C and FAM83H in OS group achieved 0.9475/1, 0.971897/1 and 0.9454545/0.8974359 specificity/sensitivity in distinguishing short survivors from long survivors, respectively. Moreover, a high mutation rate of FAM83 family (51%) was also observed in lung adenocarcinoma (LUAD) patients, and genetic alteration in the FAM83 family was associated with shorter OS and DFS in LUAD patients. Conclusions: Our results indicated that FAM83A /H might play important roles in NSCLC tumorigenesis and could be risk factor for the survival of NSCLC patients.